A retrospective study exploring parents’ perceptions of their child’s assessment - Aschieri, Filippo; Cera, Giulia; Fiorelli, Elisabetta; Brasili, Sara (Frontiers in Psychology, 2024)
The current study investigates parents' perceptions of their child's assessment, focusing on their responses to the Italian version of the Parents' Experience of Assessment Scale (QUEVA-G; Aschieri, Brasili, Cavallini & Cera; submitted). Twenty parents, who voluntarily agreed to be contacted after completing the questionnaire, participated in qualitative interviews to gain deeper insights into their assessment experiences. A thematic analysis was conducted on the interview transcriptions, highlighting three primary domains of parental experience: 1) parental perceptions of the assessment process; 2) effects of the assessment; and 3) parental perceptions of their relationship with their children's teachers. The findings indicate that QUEVA-G accurately captures most areas of interest, while also revealing unexplored aspects.